The Effect of Leadership Style, Work Motivation and Discipline of Work on Employee Performance in Pd. Highway Market Makassar - Damayanty, Devy; Marjuni, Sukmawati; Ruslan, Muhlis (Indonesian Journal of Business and Management, 2018)
This study aimed to analyze the effect of Leadership Style, Work Motivation and Work Discipline on Employee Performance In PD.Pasar Makassar Raya. The data used in this study is the primary data obtained from the questionnaire. The method used in this research is quantitative analysis. The population in this study were 156 PD.Pasar Makassar Raya employees. Sampling using Slovin formula and obtained as many as 61 respondents. Data collection techniques used are questionnaires and data analysis techniques used is multiple linear regression with SPSS 24.0 for windows. The results showed that the variables of leadership style, work motivation and work discipline have a positive and significant impact on employee performance on PD. Pasar Makassar Raya. From the test results 1) the leadership style has a positive and significant effect on the performance; 2) the work motivation has a positive and significant effect on the performance; 3) then the work discipline has a positive and significant effect on performance.